2022
DOI: 10.1111/nuf.12717
|View full text |Cite
|
Sign up to set email alerts
|

The predictive effect of self‐compassion on relationship satisfaction and conflict resolution styles in romantic relationships in nursing students

Abstract: Background People who are compassionate to both themselves and others want to alleviate their experiences of pain and those of others. Aims This study aims to evaluate the predictive effect of self‐compassion on relationship satisfaction and conflict resolution styles in romantic relationships in nursing students. Methods The sample of this study consists of 356 nursing students. The data are collected by using the Self‐Compassion Scale, the Conflict Resolution Styles Scale in Romantic Relationships, and the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…In line with our expectations, general self‐compassion was robustly related to global relationship satisfaction and to almost all the facets of relationship satisfaction. These findings are in line with previous research on the link between self‐compassion and global relationship satisfaction on an intrapersonal level (Jacobson et al, 2018; Kaya et al, 2022; Neff & Beretvas, 2013). Thus, within partners, self‐compassion seems to be a resource for experiencing a happy relationship.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with our expectations, general self‐compassion was robustly related to global relationship satisfaction and to almost all the facets of relationship satisfaction. These findings are in line with previous research on the link between self‐compassion and global relationship satisfaction on an intrapersonal level (Jacobson et al, 2018; Kaya et al, 2022; Neff & Beretvas, 2013). Thus, within partners, self‐compassion seems to be a resource for experiencing a happy relationship.…”
Section: Discussionsupporting
confidence: 92%
“…Tandler et al (2021) showed that self-compassion in adults between the ages of 30 to 55 is linked to relationship satisfaction. Self-compassion's association with relationship satisfaction was further supported by other studies that used samples of undergraduate students (Baker & McNulty, 2011;Jacobson et al, 2018;Kaya et al, 2022).…”
Section: Self-compassion In Romantic Relationshipssupporting
confidence: 61%
See 1 more Smart Citation
“…In previous research specifically with nurses, it was reported that self-compassion was positively associated with job satisfaction and negatively related to burnout ( 70 ). Further, self-compassion was an important predictor of relationship satisfaction and conflict resolution ( 71 ) and family functioning ( 72 ) among nurses. The study’s second set of hypotheses is as follows:…”
Section: Literature Reviewmentioning
confidence: 99%